جدید غذاؤں کا شریعت اسلامیہ اور طب کی روشنی میں تحقیقی جائزہ: A CRITICAL ANALYSIS OF MODERN FOODS IN THE LIGHT OF MEDICAL SCIENCE AND ISLAMIC SHARIAH - Abdur Raheem; Altaf Hussain Langrial, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
This article is an investigation about modern foods and their effects on human body and health according to medical science and Islamic Shariah. One man's life is becoming very busy and hectic due to tide schedule, and he has become a machine in this materialistic world. Due to this, he has very little time about his health and dining. He prefers those meals which he may eat in a short span of time. Moreover, those food should be easily available at any time and at any place and those food must be inexpensive and economical. Unfortunately, modern foods cover all these prerequisite qualities.  That is why, people desire to eat these modern foods i.e. fast foods, junk foods and processed foods etc. These foods are delicious and tasty too and people becomes habitual to use them. Therefore, most of the people in the world are using these foods regularly on daily basis. These foods are harmful for human health and causing serious diseases i.e. obesity, hypertension, diabetes etc. in mankind. This situation demands appropriate proper guidance, education and briefing about these modern foods so that the usage of these foods could be eliminated. This article emphases on these issues and elaborate its disadvantages according to medical science and Islamic Shariah. Furthermore, this article intricates that usage of these foods is permissible in Islamic Shariah or not.